Placental Infection with Different SARS-CoV-2 Variants Leading to Stillbirth: Report of Two Cases - Miriam A. Snow; Medini K. Annavajhala; Sofia Z. Moscovitz; Anne-Catrin Uhlemann; Larisa Debelenko (COVID, 2025)
SARS-CoV-2 placental infection, also known as placentitis (SP), is an established cause of stillbirth; however, this pathology is rare and its incidence across different viral variants is unknown. We report two new cases of SP-associated stillbirth in the third trimester of pregnancy. The cases were identified by a retrospective review of 84 fetal autopsies performed at our institution from 1 March 2020 to 1 March 2024. In one case, the mother was previously healthy and asymptomatic for COVID-19. In the second case, the mother had a history of multiple sclerosis (MS) and suffered recurrent moderate-to-severe COVID-19. In both cases, the placentas showed SP with massive perivillous fibrin deposition (PVFD), involving more than 90% of placental discs, resulting in placental insufficiency and lethal hypoxic–ischemic injury to the fetuses. Placental tissues were positive for SARS-CoV-2 by in situ hybridization (ISH) and immunohistochemistry (IHC). Sequencing revealed the delta variant in Case 1 and omicron XBB.1.515 in Case 2. The data demonstrate that SP, albeit rare, continues to cause intrauterine fetal demise (IUFD) across viral variants regardless of the clinical severity of the infection. The persistence of rare cases of SP as COVID-19 becomes globally endemic emphasizes the importance of disease prevention in pregnancy.